EKONOMI BERBASIS KEARIFAN LOKAL: STUDI DESA WISATA SUKALASANA KABUPATEN GARUT - Atu Setiati (RELASI : JURNAL EKONOMI, 2023)
The village is the axis of economic development in the welfare of the community, Sukalaksana Village is a village that was originally backward and entered into a poor village in Garut Regency. Poverty occurs because based on the geographical location of the remote Sukalaksana village, traditional farmers, and the mindset of the people who want instant, the potential of the village has not been explored. This study uses qualitative methods with data collection techniques through observation, literature review, and direct interviews with the village government, tourism village managers and BUMDes Binalaksana, local communities, and the Garut Regency Community and Village Empowerment Service. The results of this study indicate that through a tourism village program based on ecology and education village, Sukalaksana Village becomes a pilot village because it can improve the economy by empowering the community in economic development. Local wisdom from typical products, rural architecture, and local culture that are used as village potentials can be developed to support the creative economy so that poverty in the village can be resolved properly as a solution in alleviating poverty in the village. Keywords: Economy, Local wisdom, Tourism Villages